2012
DOI: 10.1186/1476-511x-11-42
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vitamin D supplementation on plasma lipid profiles: A meta-analysis of randomized controlled trials

Abstract: Observational studies have shown that low serum levels of vitamin D have been associated with an atherogenic lipid profile. However, the intervention studies gave divergent results. We conducted a meta-analysis of randomized controlled trials that evaluated the effects of vitamin D supplementation on blood lipids. A systematic literature search was conducted via MEDLINE, Cochrane library, and EMBASE for randomized controlled clinical trials assessing the effects of vitamin D supplementation on lipids. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
153
7
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(175 citation statements)
references
References 38 publications
(53 reference statements)
13
153
7
2
Order By: Relevance
“…22,29 Contrasting was Wang H study where no therapeutic value of Vitamin D supplementation on lipid profile was found. 30 In our study Vitamin D level was inversely co-related with significant CAD angiographically (P=0.02). VDD had significant association in SVD (P=0.046), DVD (P=0.017) and TVD (P=0.012) similar to Syal SK study.…”
Section: Discussionsupporting
confidence: 53%
“…22,29 Contrasting was Wang H study where no therapeutic value of Vitamin D supplementation on lipid profile was found. 30 In our study Vitamin D level was inversely co-related with significant CAD angiographically (P=0.02). VDD had significant association in SVD (P=0.046), DVD (P=0.017) and TVD (P=0.012) similar to Syal SK study.…”
Section: Discussionsupporting
confidence: 53%
“…Calcium also plays an important role in glucose uptake by binding to the skeletal cells receptors, insulin receptor affinity, and insulin sensitivity [17]. In a review study by Hao Wang et al, on 12 clinical trials, the mean change of LDL was 3.23 mg/ dL (0.55 to 5.90 mg/dL), while no changes were detected in the level of total cholesterol, TG, and HDL after the administration of vitamin D. However, they suggested further studies to confirm the effect of vitamin D on serum lipid profile [18]. As observed, results of their study were consistent with those of the current study in terms of LDL, HDL, and TG, except for cholesterol, which significantly decreased in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of previous intervention trials did not report a significant increase in HDL-C or a decrease in unfavourable serum lipids, such as TAG, TC or LDL-C, due to vitamin D supplementation (34)(35)(36) . A recent meta-analysis of twelve randomised controlled trials evaluated the effects of vitamin D supplements on blood lipids and indicated that vitamin D supplementation could increase LDL-C levels, but may not have statistically significant effects on TAG, TC or HDL-C (37) . In our study, neither the use of vitamin D supplements nor the dietary intake levels of vitamin D were significantly associated with serum lipids after adjusting for sex, age, %TBF, iPTH, PAL, time spent outdoors, intake of SFA and alcohol, smoking behaviour and the use of lipid-modifying drugs (data not shown).…”
Section: Characteristics Of the Study Participantsmentioning
confidence: 99%